Viral Delivery of dsRNA for Control of Insect Agricultural Pests and Vectors of Human Disease: Prospects and Challenges - Kolliopoulou, Anna; Taning, Clauvis N. T.; Smagghe, Guy; Swevers, Luc (Frontiers in Physiology, 2017)
RNAi is applied as a new and safe method for pest control in agriculture but efficiency and specificity of delivery of dsRNA trigger remains a critical issue. Various agents have been proposed to augment dsRNA delivery, such as engineered micro-organisms and synthetic nanoparticles, but the use of viruses has received relatively little attention. Here we present a critical view of the potential of the use of recombinant viruses for efficient and specific delivery of dsRNA. First of all, it requires the availability of plasmid-based reverse genetics systems for virus production, of which an overview is presented. For RNA viruses, their application seems to be straightforward since dsRNA is produced as an intermediate molecule during viral replication, but DNA viruses also have potential through the production of RNA hairpins after transcription. However, application of recombinant virus for dsRNA delivery may not be straightforward in many cases, since viruses can encode RNAi suppressors, and virus-induced silencing effects can be determined by the properties of the encoded RNAi suppressor. An alternative is virus-like particles that retain the efficiency and specificity determinants of natural virions but have encapsidated non-replicating RNA. Finally, the use of viruses raises important safety issues which need to be addressed before application can proceed.